The markets never sleep : - Busby, Thomas L. (John Willey & Sons, 2007)
Praise for The Markets Never Sleep "An excellent primer for futures and the global financial market, a clear voice of their importance for all traders. Tom also gives an easy-to-understand professional approach to discipline, money management, and the 'numbers' to watch that indicate market direction.